IgA‐dominant extracapillary proliferative glomerulonephritis following Escherichia coli sepsis in a renal transplant recipient. Issue 5 (15th June 2018) - Basic‐Jukic, Nikolina; Coric, Marijana; Kastelan, Zeljko
Abstract: Postinfectious glomerulonephritis (PIGN) generally occurs in association with staphylococcal infection. We present the first reported case of IgA‐dominant PIGN after Escherichia coli infection in a renal‐transplant recipient. A 65‐year‐old patient with stable allograft function and E. coli urosepsis was treated with ciprofloxacin for 2 weeks with excellent response. One week later he developed proteinuria 16 g/day. Renal biopsy finding revealed IgA‐dominant PIGN. He received steroid pulses and intravenous imunoglobulins without effect and had started with hemodialysis.